2016
DOI: 10.1111/jam.13164
|View full text |Cite
|
Sign up to set email alerts
|

The composition, localization and function of low-temperature-adapted microbial communities involved in methanogenic degradations of cellulose and chitin from Qinghai-Tibetan Plateau wetland soils

Abstract: Aims: To reveal the microbial communities from Qinghai-Tibetan Plateau wetland soils that have the potential to be used in the utilization of cellulosic and chitinous biomass at low temperatures (≤25°C). Methods and Results: Soil samples collected from six wetlands on QinghaiTibetan Plateau were supplemented with or without cellulose and chitin flakes, and anaerobically incubated at 25 and 15°C; high-throughput 16S rRNA gene sequencing was used to access the composition and localization (in the slurry and on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 93 publications
(87 reference statements)
2
35
0
Order By: Relevance
“…Seib et al conducted a study on municipal wastewater in a 10°C biogas fermentation system and found Clostridium as the main dominant bacterial genus. The same genus was reported as being dominant when Dai et al used wetland soil of the Qinghai‐Tibet Plateau as inoculum to ferment cellulose and chitin at 15°C. Bialek et al used dairy farm wastewater as raw material to carry out low‐temperature biogas fermentation at 10°C and reported that Clostridium aminobutyricum was the most abundant bacterial species.…”
Section: Discussionmentioning
confidence: 88%
“…Seib et al conducted a study on municipal wastewater in a 10°C biogas fermentation system and found Clostridium as the main dominant bacterial genus. The same genus was reported as being dominant when Dai et al used wetland soil of the Qinghai‐Tibet Plateau as inoculum to ferment cellulose and chitin at 15°C. Bialek et al used dairy farm wastewater as raw material to carry out low‐temperature biogas fermentation at 10°C and reported that Clostridium aminobutyricum was the most abundant bacterial species.…”
Section: Discussionmentioning
confidence: 88%
“…2); therefore, P1724 should belong to an anaerobe as well. So far, only few studies focused on chitin degradation in cold-area wetlands under anoxic conditions although anaerobic fermentation of chitin could be one of the important processes of nitrogen cycling in such environments [22,26,27]. Using the next-generation metagenomic method, we found this novel chitinases P1724 and avoided culturing the cold-favoring chitinolytic anaerobes, such as Paludicola psychrotolerans, which were normally hard to handle and very slow-growing [28].…”
Section: Discussionmentioning
confidence: 97%
“…After subcultured repeatedly for two years, the microbiome was collected by centrifugation and used for next-generation metagenomic sequencing. For more detailed information on sample processing, please refer to our previous publication [22].…”
Section: Microbial Consortium Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we reported the first metagenome-sourced chitinase that contained two GH18 catalytic domains. In our previous study, we found the microbial communities from the Qinghai-Tibetan Plateau wetland soils could effectively convert chitin to methane at low temperatures [25]. We continued to anaerobically enrich the microbial community from Haiyan wetland soil with chitin flakes as a sole carbon resource, and then next-generation metagenomic sequencing was done on the community.…”
Section: Introductionmentioning
confidence: 99%